Assessment of effectiveness and utilization of printing machines - Kar, Ajvit; Pal, Arun Kiran (Journal of Print and Media Technology Research, 2023)
Maintenance has become increasingly important in the production planning and management strategies of some companies. Overall equipment effectiveness is widely used for performance indicator in manufacturing industries around the world. Print productions are also not apart from problems related to the effectiveness of the machines/ equipment caused by the six big losses like breakdown losses, setup and adjustment losses, idle and minor stoppage losses, reduced speed losses, process defect losses and reduced yield losses. This can be seen with the frequency of failures that occurs in the machines because of several types of downtime so that the production target is not achieved. Total productive maintenance is the best method that can be used to improve the productivity and effi- ciency of the plant productions by using the machine effectively. Print production largely depends on the reliability, availability and maintainability of sophisticated printing machines. Aim of the present study is to determine quanti- tatively overall effectiveness and utilization of some printing equipment. The results of the effectiveness of web-offset printing machine and other ancillary equipment like computer-to-plate (CTP) machines and exposure unit are found to be below ‘world standard’ value of 85 %. The cause of low effectiveness value was due to poor performance and availability of the machines. Equipment utilization is also needed for the evaluation of printing equipment necessity,appropriateness and efficiency of the usage in print production. The proposed methodology may be able to increase the amount of working printing equipment by implementing proper maintenance planning. A significant increment of OEE (2.93 %) for web-offset printing machine is observed after implementation of proposed maintenance planning. The methodology is also validated by failure probability and reliability of the machines.